Weekend Effect Pada Indeks Harga Saham Gabungan (Ihsg) Indonesia Pasca Krisis - Kevin Chanry; Wilson Wilson (Bina Ekonomi, 2019)
Weekend effect is a form of inefficiency that makes stock returns are not random (predictable) and repetitive which is against the efficient market theory by Fama (1991). This study aims to encourage stock investor knowledge about these anomalies, and act more measurably, so that a more efficient market can be achieved. This study uses a regression method that is looking for a significant value between days against the daily return index with the aim of finding a trading pattern on a particular day, especially on Monday and Friday. As a result, the weekend effect occurs during the post-crisis impact on the real sector, in other words affect the performance of the company's stock returns as a whole so that the global financial crisis that is post-crisis 2007-2008 has a negative statement on the weekend effect.Keywords: weekend effect; post crisis; return; efficient market; anomaly market